2010
DOI: 10.1259/bjr/31573847
|View full text |Cite
|
Sign up to set email alerts
|

Practical guidelines for routine intensity-modulated radiotherapy verification: pre-treatment verification with portal dosimetry and treatment verification within vivodosimetry

Abstract: ABSTRACT. The purpose of this work is to provide guidelines for the routine use of portal dosimetry and in vivo diode measurements to verify intensity-modulated radiotherapy (IMRT) treatments. To achieve tolerance levels that are sensitive enough to intercept problems, both the portal dosimetry and the in vivo procedure must be optimised. Portal dosimetry was improved by the introduction of an optimised twodimensional (2D) profile correction, which also accounted for the effect of backscatter from the R-arm. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 34 publications
3
38
0
Order By: Relevance
“…While commissioning the method available in our clinic (Varian's Portal Dose Image Prediction (PDIP) algorithm (Varian Medical Systems, Inc., Palo Alto, CA)), an asymmetric radial response in the portal imager due to backscatter from the imager arm was observed. It led to differences on the order of 2%–3% for simple square fields (<20×20cm2) when comparing the measured to predicted portal fluences, which has also been noted by other authors 15 , 16 , 17 , 18 , 19 , 20 . However, the asymmetric response due to the backscatter from the arm is just one problem.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…While commissioning the method available in our clinic (Varian's Portal Dose Image Prediction (PDIP) algorithm (Varian Medical Systems, Inc., Palo Alto, CA)), an asymmetric radial response in the portal imager due to backscatter from the imager arm was observed. It led to differences on the order of 2%–3% for simple square fields (<20×20cm2) when comparing the measured to predicted portal fluences, which has also been noted by other authors 15 , 16 , 17 , 18 , 19 , 20 . However, the asymmetric response due to the backscatter from the arm is just one problem.…”
Section: Introductionsupporting
confidence: 51%
“…Many authors have suggested methods to correct one or both of these problems by either changing the prediction model 16 , 19 or by modifying how the images are acquired 15 , 17 , 18 , 20 . Greer et al (16) provided a 2D image of the backscatter component of the Varian Exact arm that they determined from measurements with the EPID on and off the support arm.…”
Section: Introductionmentioning
confidence: 99%
“…The dosimetric calibration of the imager panel was performed at a source imager distance of 100 cm and included a two dimensional profile correction 64,65 instead of the official profile correction based on a diagonal 40 Â 40 cm 2 field profile measurement at d max .…”
Section: Iic2 Portal Dosimetrymentioning
confidence: 99%
“…Images obtained on real patient plans yield similar results, albeit on more complex looking images. The gamma distribution was calculated with 3%, 3mm criteria and-adapting previously established acceptance scores for IMRT fields 65 to the new gamma calculation options in the 8.9 software versionrequesting 95% of the in-field points to be within these limits. Whereas some images yield near-perfect gamma scores [e.g., Fig.…”
Section: Iiic2 Portal Dosimetrymentioning
confidence: 99%
“…Alaei et al 17 cite diode agreement to within 10% of the planned dose on 76% of 300 treatment beams. Vinall et al 18 cite the use of diodes as a complementary check to EPID dosimetry in a study involving 80 patients and 437 IMRT fields. Measured diode doses were within 5% of those expected for 95% of IMRT fields, representing excellent agreement, but the technique required considerable preparation which may not be considered sustainable in many departments.…”
Section: Diodesmentioning
confidence: 99%